2019
DOI: 10.2147/ndt.s228501
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improvement Of Frontal Lobe Dysfunction And White Matter Integrity By rTMS In Treatment-Resistant Depression</p>

Abstract: AimThe impairment experienced by many individuals with depression is closely related to the cognitive symptoms of the disorder. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive brain stimulation method providing a promising technique for improving cognitive symptoms in treatment-resistant depression (TRD). In the present study, we investigated whether a relationship exists between improvements in frontal lobe dysfunction induced by rTMS and improvement of white matter integrity revealed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…After real rTMS, the authors also found increased FA in the left middle frontal gyrus whereas Tateishi et al . (2019) found higher FA values in the right superior frontal gyrus. Interestingly, Tateishi et al .…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…After real rTMS, the authors also found increased FA in the left middle frontal gyrus whereas Tateishi et al . (2019) found higher FA values in the right superior frontal gyrus. Interestingly, Tateishi et al .…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, Tateishi et al . (2019) observed increased FA only in rTMS non-responders. In contrast, Peng et al .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations